Reproductive cycle of Bolinus brandaris (Gastropoda: Muricidae) in the Gulf of Gabès (southern Tunisia) - ELHASNI, K.; VASCONCELOS, P.; GHORBEL, M.; JARBOUI, O. (Mediterranean Marine Science, 2013)
The reproductive cycle of the purple dye murex (Bolinus brandaris) from the Gulf of Gabès was studied through gonad histology and calculation of bio-physiological indices (general condition index - K and gonadosomatic index - GSI). The shell length at first sexual maturity (SL50) of B. brandaris was also investigated using a macroscopic maturation scale. The population sex ratio was statistically unbalanced (M:F = 1:1.5), with a significant dominance of females. Monthly variation in gonad maturation stages, K and GSI revealed that B. brandaris has an annual reproductive cycle, long period of gonadal activity and slight asynchrony between sexes. The spawning season extended between April and July, with a clear spawning peak from May to June. The SL50 was reached at 56.4 mm in females and 54.6 mm in males. At present, B. brandaris has no commercial value in Tunisia, but it is predictable that it will become a fishery-exploited species in the near future. The present data, particularly the timing of spawning season and the size at first sexual maturity, constitute baseline information for the proposal of fishery management measures, aiming to ensure sustainable exploitation and long-term preservation of this alternative fishing resource.